Brucellosis: a devastating disease for Indian farmers - Swami, Sourabh; Kumari, Archana; Kaushik, P (Indian Farming, 2022)
Brucellosis is a devastating disease caused by Brucella. It is capable of infecting both animals and humans. Infection in dairy animals, viz. cattle, goat, sheep leads to huge losses. The disease can be prevented by timely vaccination and preventing direct contact with infected animals.